Pengaruh Umur Perusahaan, Ukuran Perusahaan Dan Kepemilikan Institusional Terhadap Nilai Perusahaan : Studi Empiris pada Perusahaan Sub Sektor Perdagangan Eceran yang terdaftar di Bursa Efek Indonesia Periode 2019 – 2021 - Rista Devitriana, Ni Wayan; Indraswarawati, Sang Ayu Putu Arie; Yuniasih, Ni Wayan (UNHI Press, 2025)
This study examines how company age, size, and institutional ownership affect company value for retail trade sub-sector companies listed on the Indonesia Stock Exchange from 2019 to 2021). This study used Indonesia Stock Exchange retail trade sub-sector companies. This study used multiple linear regression analysis on 54 purposive-sampled financial statements. This study found no correlation between firm age and value. Firm value decreases significantly with firm size. Institutional ownership significantly reduces firm value. According to the research, companies will need to improve their shareholding composition in the future. Test results show that large institutional investors can cause corporate decision-making inconsistencies.